2000
DOI: 10.3758/bf03200266
|View full text |Cite
|
Sign up to set email alerts
|

Response strength and temporal control in fixed-interval schedules

Abstract: Pigeons responded in a two-component peak procedure in which the components differed in terms of reinforcement magnitude (Experiment 1), immediacy (Experiment 2), or probability (Experiment 3). The prediction of behavioral momentum theory that responding in the relatively richer component should be more resistant to change was tested by (1) presenting response-independent food in the intervals between components according to a variable-time (VT) schedule, (2) prefeeding, and (3) extinction. In all the experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
88
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(117 citation statements)
references
References 33 publications
24
88
5
Order By: Relevance
“…The finding that the effects of reinforcer magnitude on response rate and rate dependency do not covary stands at odds with the findings of Grace and Nevin (2000) using the peak interval procedure. It is possible that rate dependency is not related to temporal control in the same way as the peak interval procedure.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…The finding that the effects of reinforcer magnitude on response rate and rate dependency do not covary stands at odds with the findings of Grace and Nevin (2000) using the peak interval procedure. It is possible that rate dependency is not related to temporal control in the same way as the peak interval procedure.…”
Section: Discussioncontrasting
confidence: 58%
“…Additionally, Grace and Nevin (2000) showed that associative relationships determining resistance to change of overall responding may extend to the temporal organization of behavior. Given that rate dependency may be understood as a loss of temporal organization in schedule-controlled behavior, and our general procedures are similar to those used to examine resistance to change, a resistance-to-change interpretation presents itself as an attractive account for our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean of the distribution of response rates averaged over empty trials (peak time) is then perhaps a better measure of timing than wait time because motivational variables are assumed to affect only the height and spread of the response-rate distribution, not its mean. This assumption is only partially true (Grace & Nevin 2000, MacEwen & Killeen 1991, Plowright et al 2000.…”
Section: Interval Timingmentioning
confidence: 99%